Total phenolic content and in vitro photoprotective activity of ethanolic extract of torch ginger (Etlingera elatior) - Fahmi, Fawnia Alma Arabella; Rehana, Rehana; Pudyastuti, Beti (Acta Pharmaciae Indonesia, 2023)
Background: Previous research highlighted the photoprotective potential of various extracts from torch ginger leaves, but the efficacy of ethanolic extracts, particularly from leaves and other plant parts, remained unexplored. Objective: This study aimed to assess the total phenolic content and SPF value of ethanolic extracts from torch ginger leaves, flowers, and stems, comparing these with a known photoprotective agent, oxybenzone. Method: Ethanolic extraction was performed on approximately 200 grams of each plant part. The total phenolic content was determined using the Folin-Ciocalteu method, while SPF values were measured spectrophotometrically between 290 and 320 nm. Statistical analysis involved Kruskal-Wallis tests followed by post-hoc Fisher's LSD. Results: The leaf extract exhibited the highest phenolic content (483.788 ± 2.57 mg GAE/g) and SPF value at 1000 ppm, surpassing that of flowers, stems, and the positive control, oxybenzone. The correlation between phenolic content and SPF value across plant parts was statistically significant. Conclusion: The ethanolic extract of torch ginger leaves shows superior photoprotective potential, indicated by its high phenolic content and SPF value, suggesting its promising application in natural sunscreen formulations up to the permissible active substance limit of 6% set by BPOM.